THE EFFECT OF EDUCATION LEVEL AND PUBLIC KNOWLEDGE ABOUT THE USE OF ANTIBIOTICS IN UMBULHARJO YOGYAKARTA - Mexsi Mutia Rissa; Orviana Hara Aily; Danang Yulianto (FORTE JOURNAL, 2023)
Antibiotics are one of the drugs used by the public in self-medication. 27.8% kept antibiotics at home. The existence of antibiotics for self-medication shows irrational use of drugs. Meanwhile, many antibiotics were stored in households, 86.1% of which were obtained without a doctor's prescription or doctor's examination. The purpose of this study was to determine the effect of the level of education and public knowledge about the use of antibiotics in Umbulharjo, Yogyakarta. The research method used is This study used a non-experimental descriptive analytic method with a cross sectional approach. The samples taken were 89 respondents, the sampling technique used was purposive sampling. This research is explorative in nature and data is obtained through a questionnaire. The research data was carried out by the Spearman rank test. The results of this study indicate that the demographic characteristics of the Umbulharjo community show that the highest age with a percentage of 42.70% and the most sexed people are women with a percentage of 58.42%. The education level of the most respondents is Senior High School 49.45%. Respondents have the highest level of knowledge with sufficient knowledge as much as 48.31% and the level of education of respondents has no effect on the level of public knowledge about antibiotics.